Readings on tourism and hospitality - Kasim, Azilah (Universiti Utara Malaysia Press, 2007)
This book of readings presents a collection of empirical research in various disciplines related to tourism and hospitality. As such, it contains a wealth of knowledge, most of which are new findings and insights within the context of developing countries. Its multidisciplinary nature ensures that readers continue to be engaged. They will also find pleasure in discovering the various facets of the highly fragmented tourism and hospitality industry. This book is particularly useful for young researchers looking to gain knowledge in a particular area of tourism and hospitality research; and become familiar with aspects of research writing such as the techniques of writing up methodologies, reviewing the literature and discussing research findings. In Volume two, readers will have the opportunity to read work from various scholars specialising in Legal and Safety Issues, Planning and Design in Tourism and Strategic Management and Quality.